PDMS/MWCNT nanocomposite actuators using silicone functionalized multiwalled carbon nanotubes via nitrene chemistry - Yadav, Santosh Kumar; Kim, Il Jin; Kim, Hyun Ji; Kim, Joohoon; Hong, Soon Man; Koo, Chong Min (ROYAL SOC CHEMISTRY, 2013)
We demonstrate that covalently functionalized multiwalled carbon nanotubes (MWCNT) with a silicone copolymer via nitrene chemistry can be used as efficient conductive fillers for silicone dielectric elastomer actuators. The MWCNTs were covalently functionalized with poly(azidopropylmethyl)-co-(dimethylsiloxane) (silicone-N-3) bearing an azide group through a nitrene addition reaction. The incorporation of a small amount of the uniformly silicone grafted MWCNTs (silicone-g-MWCNTs) in silicone dielectric elastomer strongly enhanced the mechanical, dielectric, and electromechanical properties of the resulting nanocomposites. This reinforcing effect is attributed to the homogeneous dispersion of silicone-g-MWCNTs in the silicone elastomer matrix due to the large degree of compatibility between the matrix and the passivation layers of the functionalized MWCNT.
Keywords: TRANSFER RADICAL POLYMERIZATION; HIGH DIELECTRIC-CONSTANT; ELECTRIC ACTUATION; COMPOSITES; ELASTOMERS; POLYURETHANE; PERFORMANCE; GRAPHENE; FILLER